근접방사선치료용 다목적 팬톰을 이용한 직장 내 선량분석 - 허현도(Hyun Do Huh), 김성훈(Seong Hoon Kim), 조삼주(Sam Ju Cho), 이석(Suk Lee), 신동오(Dong Oh Shin), 권수일(Soo il Kwon), 김현정(Hun Jung Kim), 김우철(Woo Chul Kim), 노준규(John J K Loh) (Radiation oncology journal, 2005)
KCI Citation Count: 3